Pengembangan Pengembangan Media Papan Pintar Pancasila Berbasis Permainan Tradisional Pada Pembelajaran PPKn Sebagai Penguatan Profil Pelajar Pancasila Elemen Gotong-royong SDN Tlumpu Kota Blitar - Ramadhani, Muhammad; Alfi, Cindya; Fatih, Mohamad (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The Pancasila Student Profile now makes students more creative and innovative to shape and create themselves into students who are religious and can respect others. Accompanied by interesting learning created by teachers and the school environment as well as learning media that are popular and not boring for students. One learning method that can be used is the Pancasila smart board. This study was conducted to determine the level of validity, feasibility and strengthening of the Pancasila student profile, especially the mutual cooperation element. This research and development uses the ADDIE development model which includes stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The instruments used in this research were observation, interviews, questionnaires and documentation. The research results are also documented showing that the level of validation carried out by material experts and media experts is in the very valid category. The level of eligibility carried out by the class IV homeroom teacher at SDN Tlumpu, Blitar City was categorized as very valid. Strengthening the Pancasila student profile, the mutual cooperation element is included in the strong qualifications. So there is a possibility that this media is suitable for use. as a learning medium. In this research, data was collected through questionnaires which obtained the following results: validation questionnaire for material experts and media experts with an average of 85.9%, feasibility questionnaire with a percentage of 100% and questionnaire strengthening the profile of Pancasila students with mutual cooperation elements for class students IV Tlumpu Elementary School, Blitar City 98.2% in the "Strong" category.